Do White Law Enforcement Officers Target Minority Suspects?. (19th June 2018) - Menifield, Charles E.; Shin, Geiguen; Strother, Logan
Abstract: The debate over possible bias in the use of deadly force has recently been exacerbated by highly publicized killings of African American males around the country. While much research has been conducted examining police behavior, little has been done to investigate the impact of race on police behavior. This article aims to answer this question: are white police officers more likely to use lethal force on minority suspects or people of a specific race? To answer this question, the authors construct a data set of all confirmed uses of lethal force by police officers in the United States in 2014 and 2015. They find that although minority suspects are disproportionately killed by police, white officers appear to be no more likely to use lethal force against minorities than nonwhite officers .